2023
DOI: 10.1371/journal.pbio.3002158
|View full text |Cite
|
Sign up to set email alerts
|

The Brain/MINDS Marmoset Connectivity Resource: An open-access platform for cellular-level tracing and tractography in the primate brain

Abstract: The primate brain has unique anatomical characteristics, which translate into advanced cognitive, sensory, and motor abilities. Thus, it is important that we gain insight on its structure to provide a solid basis for models that will clarify function. Here, we report on the implementation and features of the Brain/MINDS Marmoset Connectivity Resource (BMCR), a new open-access platform that provides access to high-resolution anterograde neuronal tracer data in the marmoset brain, integrated to retrograde tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Starting with studies in rodents (Oh et al, 2014; Kim et al, 2017; Bjerke et al, 2020), the traditional approach of investigating areas and nuclei one or a few at a time is being complemented by projects involving larger datasets, and focused on unveiling organizational principles, often relying on multiple techniques. Such approaches have recently made their way to the brains of non-human primates, revealing new information based on single-neuron resolution connectivity (Majka et al, 2020; Skibbe et al, 2023) and transcriptomics (Krienen et al, 2020, 2023; Chen et al, 2023), sometimes combined with non-invasive imaging (Liu et al 2020; Tian et al, 2022). However, one missing link in these efforts has been their relation to the traditionally recognized cell types of the mammalian cortex, for which a wealth of cytological and physiological knowledge is available, and which are central to the generation of biophysically realistic models of brain function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with studies in rodents (Oh et al, 2014; Kim et al, 2017; Bjerke et al, 2020), the traditional approach of investigating areas and nuclei one or a few at a time is being complemented by projects involving larger datasets, and focused on unveiling organizational principles, often relying on multiple techniques. Such approaches have recently made their way to the brains of non-human primates, revealing new information based on single-neuron resolution connectivity (Majka et al, 2020; Skibbe et al, 2023) and transcriptomics (Krienen et al, 2020, 2023; Chen et al, 2023), sometimes combined with non-invasive imaging (Liu et al 2020; Tian et al, 2022). However, one missing link in these efforts has been their relation to the traditionally recognized cell types of the mammalian cortex, for which a wealth of cytological and physiological knowledge is available, and which are central to the generation of biophysically realistic models of brain function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our major finding, however, was the observed dynamics of neuronal responses following sound stimuli within area 32, in which an initially non-selective reduction in neural activity was followed by an increase in activity that conveyed sound selectivity. Retrograde tracer injections have revealed that in addition to projections from other prefrontal areas 18 , area 32 receives significant input from two other primary sources: the basolateral (BLA) and basomedial amygdala (BMA), and higher auditory and association areas, such as the temporopolar area (TPO) and the superior temporal region (STR) 19 . In rodents, the excitatory projection from the amygdala is known to activate local circuit inhibitory interneurons in the mPFC which then are thought to suppress neural activity within the area 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The discrimination time was defined as the beginning of the first 50 ms window when the activity became significantly different between preferred and nonpreferred sounds (evaluated by non-paired Student t-test at p<0.025). MRI shows pre-processed retrograde tracer injection into area 32 (R01_0095) from BMCRexplorer) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding its development requires analyzing gene expression patterns across mammalian species. While rodent studies offer insight, studying primate cortical development, especially in species like the common marmoset, provides valuable clues due to their brain's similarity to humans [3][4][5][6][7][8][9][10] . Our analysis of gene expression by spatial transcriptomics, in various neocortical regions during marmoset development revealed time-speci c, region-speci c cortical layer-speci c gene expression.…”
Section: Introductionmentioning
confidence: 99%